Isolasi dan Pengklonan Gen Penyandi H+-ATPase Membran Plasma dari Melastoma malabathricum L. - ., Muzuni; Sopandie, Didy; Suharsono, Utut Widyastuti; ., Suharsono (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2014)
ABSTRACT Melastoma malabathricum L. is an Al-accumulating plant that grows well in acidic soils with high level of soluble aluminum in the tropics. One of the important proteins in the detoxifying Al stress is a plasma membrane H+-ATPase, a most abundant protein on the plasma membrane, encoded by PMA gene. The objective of this research was to isolate and characterize the gene encoding plasma membrane H+-ATPase from M. malabathricum L. Full length cDNA of MmPMA had been successfully isolated through a gradual isolation of the gene. The 5’ end and middle part of the MmPMA gene had been successfully isolated by PCR by using total cDNA as template and pma primers designed from some plants, while the 3’ end of Mmpma had been isolated by 3’ RACE. The parts of the gene had been successfully joined by PCR. The joining product was successfully inserted into pGEM-T Easy and the recombinant plasmid was successfully introduced into E. coli DH5α. Nucleotide sequence analysis showed that the length of MmPMA coding sequence was 2,871 bp encoding 956 amino acids with molecular weight of 105.29 kDa and a predicted pI value of 6.84. Local alignment analysis based on nucleotide of mRNA showed that MmPMA is 82% identical to pma Vitis vinifera; 81% to pma Juglans regia, pma Populus trichocarpa, pma Sesbania rostrata, and pma Prunus persica and 80% to pma Lycopersicon esculentum. Based on deduced amino acid sequence, MmPMA is 94% identical to PMA Vitis vinifera and PMA Juglans regia; 93% to PMA Populus trichocarpa; 92% to PMA Vicia faba, Lycopersicon esculentum, and Arabidopsis thaliana, AHA4. MmPMA has 10 transmembrane domains, 4 cytoplasm loops, 6 functional domains and 3 autoregulatory domains.Keywords: aluminum, cDNA, MmPMA, PCR, RACE